Taxonomic richness, diversity, temporal variation, and ecological aspects of fish larvae in the Gulf of Tribugá, Colombia - Rondon Ramos, Mariana (2025)
Introduction: The larval phase is critical in the fish life cycle, yet knowledge of its taxonomic identification, abundance, and temporal variation remains limited in tropical coastal environments. Objective: To identify fish larvae in the Gulf of Tribugá, Northern Pacific Colombia, and assess their temporal variability considering regional oceanographic variations. Methods: We studied fish larval assemblages during the cold and warm water periods of 2022.We collected larvae through daytime and oblique tows from 20 m depth to the surface using a 70 cm mouth cylindrical-conical net with 500 µm mesh. Results: We captured a total of 602 larvae of 89 species from 29 families, with Scombridae, Engraulidae, Nomeidae, Gerreidae, Carangidae, and Engraulidae being dominant. Key species included Auxis rochei (36.32 %), Anchoa spp. (11.77 %) and Cubiceps pauciradiatus (8.10 %) during the cold period, and Eugerres lineatus (27.04 %), Eucinostomus gracilis (5.43 %), and Sphoeroides sp.1 (4.12 %) during the warm period. Differences were found in larval assemblage structure and composition between the two periods, with a species turnover rate of 66 %. Conclusions: This study reports the presence of 89 fish species’ larval stages in the Gulf of Tribugá, with each oceanographic period presenting a distinct larval assemblage.